2004
DOI: 10.1073/pnas.0405535101
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative PRKAR1A genotype–phenotype analyses in humans with Carney complex and prkar1a haploinsufficient mice

Abstract: Carney complex (CNC) is a familial multiple neoplasia syndrome characterized by cardiac and extracardiac myxomas in the setting of spotty skin pigmentation and endocrinopathy. We previously identified PRKAR1A (regulatory subunit 1α of protein kinase A) mutations in CNC. Mutational analyses of the PRKAR1A gene in 51 unrelated CNC probands now detect mutations in 65%. All mutations, except for one unique missense mutation, lead to PRKAR1A ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 39 publications
2
122
1
Order By: Relevance
“…Others have reported that cAMP inhibits the mammalian target of rapamycin complex-1 and -2 activation via a PKAdependent mechanism 46 . In a mouse model of inherited tumour syndrome Carney complex (CNC) with defect in the regulatory subunit 1a of PKA, there is evidence that prkar1a þ / À (regulatory subunit 1a of PKA) mice developed HCC, while the PKA activity in these mice remained unchanged 47 . However, in another study, CNC patients with prkar1a mutations have been shown to develop a spectrum of carcinomas but not HCC 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that cAMP inhibits the mammalian target of rapamycin complex-1 and -2 activation via a PKAdependent mechanism 46 . In a mouse model of inherited tumour syndrome Carney complex (CNC) with defect in the regulatory subunit 1a of PKA, there is evidence that prkar1a þ / À (regulatory subunit 1a of PKA) mice developed HCC, while the PKA activity in these mice remained unchanged 47 . However, in another study, CNC patients with prkar1a mutations have been shown to develop a spectrum of carcinomas but not HCC 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Although PKAc activity is elevated in this condition, its role in the increased tumorigenesis in CNC has been questioned (21). Nevertheless, a recent study has suggested that elevated PKAc activity in the adrenal tissue of CNC patients, via activation of B-Raf, may augment the activity of MEK and Erk1/2 (44).…”
Section: Pp2a Exists In a Complex With Rsk1⅐pka⅐d-akap1 And Ht31mentioning
confidence: 99%
“…CNC is an autosomal dominant multiple neoplasia syndrome in which myxomas of the skin, heart, and/or vicera are recurrent and also associated with high incidence of endocrine and ovarian tumors as well as Schwannomas (18 -20). The majority of patients with the multiple neoplasia CNC syndrome harbor mutations in the PKAR1A gene (21) that result in PKARI␣ haploinsufficiency. Importantly, however, loss of heterozygosity or alterations in PKA activity may not contribute toward the tumorigenicity in either CNC patients or mouse model of CNC (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This gene maps to 17q22-24, a locus that has been implicated, by linkage analysis, in a dominantly multiple neoplasia inherited syndrome with many clinical and pathological manifestations, the Carney complex (CNC) (46,47). Heterozygous inactivating germline mutations of PRKAR1A have been demonstrated in about 45 -65% of CNC families (47,48). LOH at 17q22-24 is observed in tumours from CNC patients, suggesting that PRKAR1A is a tumour-suppressor gene.…”
Section: Prkar1a Gene and Locus 17q22-24mentioning
confidence: 99%